Copper-clad ceramic substrate and preparation method thereof
By cleaning and pretreating the ceramic substrate, combined with laser processing and ultrasonic vibration technology, the problem of solder overflow is solved, and the bonding performance and production yield of copper-clad ceramic plates are improved.
Patent Information
- Application Number
- CN202411982345.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the existing copper-clad ceramic plate processing technology, metal solder is prone to flow and overflow during high-temperature sintering, affecting the product appearance and mass production.
Improved preparation methods include cleaning and pretreatment of the ceramic substrate, pre-cutting the solder guide and solder troughs by laser processing, coating the transition layer and active solder layer, and using ultrasonic vibration during vacuum brazing to control the distribution of the solder.
It effectively avoids solder overflow and diffusion, improves the bonding performance between the ceramic substrate and copper foil, ensures excellent overall appearance and high yield of the product, and is suitable for mass production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-clad boards, and in particular to a copper-clad ceramic substrate and a preparation method thereof. Background Art
[0002] Copper-clad ceramics, also known as copper-clad ceramic substrates, are a type of electronic basic material made by sintering copper foil directly onto the ceramic surface using DCB (Direct Copper Bond) technology. With in-depth research and development, active metal brazing technology is currently the most commonly used copper-clad ceramic board processing technology.
[0003] Active metal brazing is a method of placing active metal powder (Ti, Zr, etc.) and metal solder (Ag, Cu) that can form an alloy with it at a certain temperature between a ceramic substrate and metal copper, and heating and melting them in a vacuum or inert atmosphere to achieve sealing between the metal copper and the ceramic substrate. However, metal solder is very likely to overflow during high-temperature sintering, affecting the overall product appearance and not conducive to mass production.
[0004] Therefore, based on this situation, the present application discloses a copper-clad ceramic substrate and a preparation method thereof to solve the technical problem. Summary of the invention
[0005] The object of the present invention is to provide a copper-clad ceramic substrate and a preparation method thereof, so as to solve the problems raised in the above background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take the ceramic substrate, ultrasonically clean it with acetone solution for 10-15 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 10-15 minutes each, and blow dry with nitrogen; (2) pre-cutting a solder guide groove on the edge of one side of the ceramic substrate, washing with deionized water, drying, and then spin-coating photoresist on the surface of the ceramic substrate, baking at 100-110° C. for 10-15 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the solder groove and the solder guide groove are connected to each other; Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence. The ultrasonic cleaning time is 10-15 minutes each, and then blow dry with nitrogen; (3) Take modified graphene, aluminum oxide, calcium carbonate, silicon carbide, and silicon nitride, mix them evenly, and then ball-mill them. Add dispersant, binder, and water, stir evenly to obtain a transition coating material, apply it to a solder tank, and sinter at a high temperature of 1500-1600°C for 30-40 minutes to obtain a transition layer. (4) Take silver powder, copper powder, titanium hydride powder and modified graphene, mix and stir evenly, grind for 5-10 minutes, and ball mill for 40-50 minutes at a speed of 160-180 r / min. After ball milling, add thickener, dispersant, solvent, antioxidant and thixotropic agent, mix and stir evenly to obtain solder; Applying solder to the solder guide groove and the solder groove, and covering the transition layer to obtain an active solder layer; (5) Repeat steps (2) to (4) to process interconnected solder grooves and solder guide grooves on the other side of the ceramic substrate, and apply a transition layer and an active solder layer, wash with deionized water, and dry; Take copper foil, fix it on both sides of the ceramic substrate, and braze it at high temperature to obtain a copper-clad board; take the copper-clad board, perform circuit patterning treatment, and etch a preset circuit pattern to obtain the copper-clad ceramic substrate.
[0007] In a more optimized solution, in step (2), the thickness of the ceramic substrate is h, the width of the solder guide groove is 0-5 mm, and the depth is ≦0.5h; the depth of the solder groove is ≦0.5h, and the depth of the solder groove is greater than the depth of the solder guide groove.
[0008] In a more optimized solution, in step (2), the thickness of the active solder layer coated in the solder trough and the solder guide trough is 30-50 μm, and the thickness of the transition layer is 5-10 μm.
[0009] According to a more optimized solution, in step (2), the depth difference between the solder groove and the solder guide groove is 5-7 μm, and the solder guide groove is formed by any one of laser processing, ultrasonic grinding, electric spark processing, and electrolytic processing.
[0010] In a more optimized solution, in step (2), the pattern of the solder groove is the same as the preset circuit pattern, and when the width of the preset circuit pattern is a, the width of the solder groove is 0.6a~0.8a.
[0011] In the optimized solution, in step (5), the high temperature brazing temperature is 900-950°C and the vacuum degree is 5×10 -4 ~8×10 - 4 Pa; ultrasonic vibration is applied to the surface of the copper foil during high-temperature brazing, the ultrasonic frequency is 20-25kHz, the power is 100-200w, and the ultrasonic time is 30-60s.
[0012] In a more optimized solution, the raw materials of the components of the transition layer include 90wt% powder and 10wt% organic solvent, the powder includes 8wt% modified graphene, 82wt% aluminum oxide, 4wt% silicon carbide, 5wt% silicon nitride, and 1wt% calcium carbonate; the organic solvent includes 4wt% dispersant, 3wt% binder and 93wt% water, the dispersant is sodium polyacrylate, and the binder is silica sol.
[0013] In a more optimized solution, the raw materials of each component in the solder include 88wt% solder powder and 12wt% organic carrier, the solder powder includes 70wt% silver powder, 20wt% copper powder, 5wt% titanium hydride powder and 5wt% modified graphene; the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent; The thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, and the solvent is diethylene glycol dimethyl ether and terpineol in a mass ratio of 2:3.
[0014] A more optimized scheme, the modified graphene preparation method is: take copper sulfate pentahydrate and silver nitrate, add graphene oxide aqueous solution, deionized water, sodium citrate and sodium borohydride after mixing, stir and react at 25-30°C for 1-2h, let stand for 2-3h after the reaction is completed, filter and wash, and vacuum dry to obtain modified graphene.
[0015] A more optimized solution is a copper-clad ceramic substrate prepared according to the above-mentioned method for preparing a copper-clad ceramic substrate.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention discloses a copper-clad ceramic substrate and a preparation method thereof. A silicon nitride ceramic substrate is used in the preparation of the copper-clad board. The silicon nitride ceramic substrate is firstly cleaned and degreased by acetone, anhydrous ethanol and deionized water in sequence to remove surface impurities. Then, a solder guide groove is pre-cut at the edge of the surface by laser processing. Then, photoresist is spin-coated on the surface of the ceramic substrate, and a solder groove pattern is exposed and developed. The solder groove pattern is consistent with a preset subsequent circuit pattern. Then, ICP etching is performed to form a solder groove, and the solder groove and the solder guide groove are connected to each other. In this process step, the application needs to meet the following parameter conditions: (1) The thickness of the ceramic substrate is h, the width of the solder guide groove is 0-5 mm, and the depth is ≤0.5h; the depth of the solder groove is ≤0.5h.
[0017] (2) The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.6a~0.8a.
[0018] (3) The depth of the solder groove is greater than the depth of the solder guide groove, and the depth difference between the solder groove and the solder guide groove is 5-7 μm.
[0019] The reason for limiting condition (1) is that the present application is used to prepare copper-clad ceramic boards. In the subsequent steps, the copper foil needs to be fixed on both sides of the ceramic substrate and vacuum brazed. To ensure its actual processing, the present application limits the depth of the solder guide groove and the solder groove to less than 0.5h to avoid the ceramic substrate from breaking or bending due to excessive etching during the subsequent processing, which affects the actual use. The width of the solder guide groove is 0~5mm. The width is limited to avoid the groove being too wide and affecting the subsequent copper foil surface circuit patterning.
[0020] (2) The reason for the limitation of the conditions is that: the present application etches a solder groove through photolithography and ICP, and the pattern of the solder groove is the same as the preset circuit pattern. Therefore, when applying solder, the present application can apply a patterned solder layer, and then fix it with copper foil to pattern the circuit. After the subsequent etching of the copper foil image circuit, there is no need to etch the solder layer again, thereby avoiding the problem of solder residue between circuits caused by the subsequent etching process and reducing the risk of circuit short circuit.
[0021] At the same time, since circuit graphic etching is required later, the etching solution will etch the copper foil and also slightly etch the solder layer under the copper foil during etching. In order to ensure the bonding strength between the copper foil and the ceramic substrate, the present application limits the width of the solder groove to 0.6a~0.8a. On the one hand, it can reduce the influence of the etching solution. On the other hand, during the subsequent vacuum brazing, active solder sometimes overflows the groove and spreads at the groove. The limitation of this width can avoid the influence of solder between the circuits to a great extent, reduce the process difficulty, and make the actual operation simpler.
[0022] (3) The reason for limiting the conditions is that the present application will subsequently coat active solder in the solder trough and solder guide groove to form an active solder layer. In order to ensure that the solder layer can be evenly distributed in the groove and to avoid solder overflow to the greatest extent, the present application limits the depth of the solder trough and solder guide groove. The depth of the solder guide groove at the edge is designed to be slightly smaller than the solder trough. In this way, when the active solder is coated, the solder can flow from the solder trough to the solder guide groove and spread, avoiding the accumulation of solder in the groove, and further reducing the process difficulty.
[0023] Based on the above-mentioned limiting conditions, the present application introduces a transition layer in the solder tank. The transition layer is a mixture of modified graphene oxide, aluminum oxide, calcium carbonate, silicon carbide, and silicon nitride, in which aluminum oxide is the main component. The transition layer is laid in a loose and porous state in the solder tank, which can improve the bonding between the active solder layer and the ceramic substrate, so that the active solder is in full contact with the bottom and surrounding of the groove, and reacts and combines during subsequent brazing, which can further improve the bonding performance between the copper foil and the ceramic substrate.
[0024] After the transition layer is coated and sintered at high temperature, the present application coats active solder in the solder trough and solder guide groove, and performs vacuum brazing. Ultrasonic vibration is used to assist in vacuum brazing. On the one hand, a uniform and dense welding surface can be formed between the copper foil and the ceramic substrate under ultrasonic vibration, thereby ensuring the bonding between the two. On the other hand, ultrasonic vibration can homogenize the high-temperature molten solder, and with the depth setting of the solder trough and solder guide groove, the solder can be distributed more evenly, greatly reducing the overflow and outward diffusion of the solder flow.
[0025] On the basis of the above scheme, the present application introduces modified graphene oxide into the transition layer and the solder. The modified graphene is graphene with surface modified with nickel and silver. The modification of its surface nanoparticles can, on the one hand, introduce alloy elements to promote the bonding between the solder and the ceramic substrate and copper foil, thereby improving its bonding performance. On the other hand, due to the properties of graphene itself, its introduction into the solder can also improve the strength and wettability of the solder.
[0026] The invention discloses a copper-clad ceramic substrate and a preparation method thereof. The process design is reasonable and the operation is simple. The prepared copper-clad plate has excellent strength, the bonding performance between the ceramic substrate and the copper foil is good, and the solder can be controlled during the processing of the copper-clad ceramic substrate to avoid overflow and diffusion. The product has an excellent overall appearance and a high yield, can be used for mass production, and has high practicality. DETAILED DESCRIPTION
[0027] The technical solutions in the examples of the present invention are described clearly and completely below. Obviously, the examples described are only part of the examples of the present invention, not all of them. Based on the examples in the present invention, all other examples obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The graphene oxide model is SE3122, provided by Changzhou Sixth Element Material Technology Co., Ltd.; the aluminum oxide particle size is 20-100 nm; the silicon carbide particle size is 10 μm.
[0029] Example 1: A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take a ceramic substrate, ultrasonically clean it with acetone solution for 10 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 10 minutes each, and blow dry with nitrogen; the ceramic substrate is a silicon nitride ceramic substrate, and its size is 50 mm×50 mm×0.32 mm; (2) Pre-cutting a solder guide groove on the edge of one side of the ceramic substrate by laser processing, wherein the width of the solder guide groove is 5 mm and the depth is 53 μm; washing with deionized water, drying, and then spin coating photoresist on the surface of the ceramic substrate, baking at 100°C for 15 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the depth of the solder groove is 60 μm, and the solder groove and the solder guide groove are interconnected.
[0030] The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.8a.
[0031] Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; (3) Take 8wt% modified graphene, 82wt% alumina, 4wt% silicon carbide, 5wt% silicon nitride, and 1wt% calcium carbonate, mix them evenly, and then ball-mill them to obtain powder, which is prepared in a ratio of 90wt% powder and 10wt% organic solvent, wherein the organic solvent includes 4wt% dispersant, 3wt% binder, and 93wt% water, and stir evenly to obtain a transition coating material, which is applied to the solder tank and sintered at a high temperature of 1500°C for 40 minutes to obtain a transition layer; the dispersant is sodium polyacrylate, and the binder is silica sol. The thickness of the transition layer is 10μm; (4) Take graphene oxide and deionized water, and ultrasonically disperse them for 20 minutes to obtain a graphene oxide aqueous solution (1 mg / mL). Take 0.25 g of copper sulfate pentahydrate and 0.16 g of silver nitrate, mix them, add 10 mL of graphene oxide aqueous solution, 20 mL of deionized water, 10 mL of sodium citrate (0.02 mol / L) and sodium borohydride (0.2 mol / L), and stir the mixture at 25°C for 2 hours. After the reaction is completed, let it stand for 2 hours, filter and wash it, and vacuum dry it to obtain modified graphene.
[0032] Take 70wt% silver powder, 20wt% copper powder, 5wt% titanium hydride powder and 5wt% modified graphene, mix and stir evenly, grind for 5min, and ball mill for 50min at a speed of 160r / min to obtain solder powder, mix 88wt% solder powder and 12wt% organic carrier in a ratio, the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent, mix and stir evenly to obtain solder; the thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, and the solvent is diethylene glycol dimethyl ether and pineneol, and the mass ratio of the two is 2:3.
[0033] The solder is coated in the solder guide groove and the solder tank, and covers the transition layer to obtain an active solder layer; the thickness of the active solder layer coated in the solder guide groove and the solder tank is 50 μm; (5) Repeat steps (2) to (4) to process interconnected solder grooves and solder guide grooves on the other side of the ceramic substrate, and apply a transition layer and an active solder layer, wash with deionized water, and dry; Take copper foil with a thickness of 50 mm × 50 mm × 0.4 mm, fix it on both sides of the ceramic substrate, and braze it at a high temperature of 900 ° C and a vacuum degree of 5 × 10 -4 Pa; applying ultrasonic vibration to the surface of the copper foil during brazing, the ultrasonic frequency is 20kHz, the power is 100w, and the ultrasonic time is 60s to obtain a copper-clad laminate; taking the copper-clad laminate, performing circuit graphic processing, etching a preset circuit pattern, and obtaining the copper-clad ceramic substrate.
[0034] Example 2: A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take a ceramic substrate, ultrasonically clean it with acetone solution for 12 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 12 minutes each, and blow dry with nitrogen; the ceramic substrate is a silicon nitride ceramic substrate, and its size is 50 mm×50 mm×0.32 mm; (2) Pre-cutting a solder guide groove on the edge of one side of the ceramic substrate by laser processing, wherein the width of the solder guide groove is 5 mm and the depth is 53 μm; washing with deionized water, drying, and then spin coating photoresist on the surface of the ceramic substrate, baking at 105°C for 12 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the depth of the solder groove is 60 μm, and the solder groove and the solder guide groove are interconnected.
[0035] The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.8a.
[0036] Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; (3) Take 8wt% modified graphene, 82wt% alumina, 4wt% silicon carbide, 5wt% silicon nitride, and 1wt% calcium carbonate, mix them evenly, and then ball-mill them to obtain powder, which is prepared in a ratio of 90wt% powder and 10wt% organic solvent, wherein the organic solvent includes 4wt% dispersant, 3wt% binder, and 93wt% water, and stirred evenly to obtain a transition coating material, which is applied to the solder tank and sintered at a high temperature of 1550°C for 35 minutes to obtain a transition layer; the dispersant is sodium polyacrylate, and the binder is silica sol. The thickness of the transition layer is 10μm; (4) Take graphene oxide and deionized water, and ultrasonically disperse them for 20 minutes to obtain a graphene oxide aqueous solution (1 mg / mL). Take 0.25 g of copper sulfate pentahydrate and 0.16 g of silver nitrate, mix them, add 10 mL of graphene oxide aqueous solution, 20 mL of deionized water, 10 mL of sodium citrate (0.02 mol / L) and sodium borohydride (0.2 mol / L), and stir the mixture at 28°C for 1.5 hours. After the reaction is completed, let it stand for 2.5 hours, filter and wash it, and vacuum dry it to obtain modified graphene.
[0037] Take 70wt% silver powder, 20wt% copper powder, 5wt% titanium hydride powder and 5wt% modified graphene, mix and stir evenly, grind for 8min, and ball mill for 45min at a speed of 170r / min to obtain solder powder, mix 88wt% solder powder and 12wt% organic carrier in a ratio, the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent, mix and stir evenly to obtain solder; the thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, the solvent is diethylene glycol dimethyl ether and pineneol, and the mass ratio of the two is 2:3.
[0038] The solder is coated in the solder guide groove and the solder tank, and covers the transition layer to obtain an active solder layer; the thickness of the active solder layer coated in the solder guide groove and the solder tank is 50 μm; (5) Repeat steps (2) to (4) to process interconnected solder grooves and solder guide grooves on the other side of the ceramic substrate, and apply a transition layer and an active solder layer, wash with deionized water, and dry; Take copper foil with a thickness of 50 mm × 50 mm × 0.4 mm, fix it on both sides of the ceramic substrate, and braze it at a high temperature of 930 ° C and a vacuum degree of 5 × 10 -4Pa; applying ultrasonic vibration to the surface of the copper foil during brazing, the ultrasonic frequency is 25kHz, the power is 100w, and the ultrasonic time is 40s to obtain a copper-clad laminate; taking the copper-clad laminate, performing circuit graphic processing, etching a preset circuit pattern, and obtaining the copper-clad ceramic substrate.
[0039] Example 3: A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take a ceramic substrate, ultrasonically clean it with acetone solution for 15 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; the ceramic substrate is a silicon nitride ceramic substrate, and its size is 50 mm×50 mm×0.32 mm; (2) Pre-cutting a solder guide groove on the edge of one side of the ceramic substrate by laser processing, wherein the width of the solder guide groove is 5 mm and the depth is 53 μm; washing with deionized water, drying, and then spin coating photoresist on the surface of the ceramic substrate, baking at 110° C. for 10 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the depth of the solder groove is 60 μm, and the solder groove and the solder guide groove are interconnected.
[0040] The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.8a.
[0041] Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; (3) Take 8wt% modified graphene, 82wt% alumina, 4wt% silicon carbide, 5wt% silicon nitride, and 1wt% calcium carbonate, mix them evenly, and then ball-mill them to obtain powder, which is prepared in a ratio of 90wt% powder and 10wt% organic solvent, wherein the organic solvent includes 4wt% dispersant, 3wt% binder, and 93wt% water, and stir evenly to obtain a transition coating material, which is applied to the solder tank and sintered at a high temperature of 1600°C for 30 minutes to obtain a transition layer; the dispersant is sodium polyacrylate, and the binder is silica sol. The thickness of the transition layer is 10μm; (4) Take graphene oxide and deionized water, and ultrasonically disperse them for 20 minutes to obtain a graphene oxide aqueous solution (1 mg / mL). Take 0.25 g of copper sulfate pentahydrate and 0.16 g of silver nitrate, mix them, add 10 mL of graphene oxide aqueous solution, 20 mL of deionized water, 10 mL of sodium citrate (0.02 mol / L) and sodium borohydride (0.2 mol / L), and stir the mixture at 30°C for 1 hour. After the reaction is completed, let it stand for 2 hours, filter and wash it, and vacuum dry it to obtain modified graphene.
[0042] Take 70wt% silver powder, 20wt% copper powder, 5wt% titanium hydride powder and 5wt% modified graphene, mix and stir evenly, grind for 10 minutes, and ball mill for 40 minutes at a speed of 180r / min to obtain solder powder, mix 88wt% solder powder and 12wt% organic carrier in a ratio, the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent, mix and stir evenly to obtain solder; the thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, and the solvent is diethylene glycol dimethyl ether and pineneol, and the mass ratio of the two is 2:3.
[0043] The solder is coated in the solder guide groove and the solder tank, and covers the transition layer to obtain an active solder layer; the thickness of the active solder layer coated in the solder guide groove and the solder tank is 50 μm; (5) Repeat steps (2) to (4) to process interconnected solder grooves and solder guide grooves on the other side of the ceramic substrate, and apply a transition layer and an active solder layer, wash with deionized water, and dry; Take copper foil with a thickness of 50 mm × 50 mm × 0.4 mm, fix it on both sides of the ceramic substrate, and braze it at a high temperature of 950 ° C and a vacuum degree of 5 × 10 -4 Pa; applying ultrasonic vibration to the surface of the copper foil during brazing, the ultrasonic frequency is 25kHz, the power is 200w, and the ultrasonic time is 60s to obtain a copper-clad laminate; taking the copper-clad laminate, performing circuit graphic processing, etching a preset circuit pattern, and obtaining the copper-clad ceramic substrate.
[0044] Comparative Example 1: Comparative Example 1 is based on Example 2. Modified graphene oxide is not introduced into Comparative Example 1, and the remaining process steps and reaction parameters are consistent with Example 2.
[0045] A method for preparing a copper-clad ceramic substrate comprises the following steps: (3) Take 90wt% alumina, 4wt% silicon carbide, 5wt% silicon nitride, and 1wt% calcium carbonate, mix them evenly, and then ball-mill them to obtain powder. Prepare the mixture in a ratio of 90wt% powder and 10wt% organic solvent, wherein the organic solvent includes 4wt% dispersant, 3wt% binder, and 93wt% water. Stir evenly to obtain a transition coating material, apply it to the solder tank, and sinter at a high temperature of 1550°C for 35 minutes to obtain a transition layer. The dispersant is sodium polyacrylate, and the binder is silica sol. The thickness of the transition layer is 10μm. (4) Take 70wt% silver powder, 20wt% copper powder, and 10wt% titanium hydride powder, mix and stir evenly, then grind for 8min, and ball mill for 45min at a speed of 170r / min to obtain solder powder, and mix 88wt% solder powder and 12wt% organic carrier in a ratio, wherein the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent, and mix and stir evenly to obtain solder; the thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, and the solvent is diethylene glycol dimethyl ether and pineneol, and the mass ratio of the two is 2:3.
[0046] The solder is coated in the solder guide groove and the solder tank, and covers the transition layer to obtain an active solder layer; the thickness of the active solder layer coated in the solder guide groove and the solder tank is 50 μm; Comparative Example 2: Comparative Example 2 is based on Example 2. In Comparative Example 2, the depth of the solder groove is 60 μm, the depth of the solder guide groove is 50 μm, and the remaining process steps and reaction parameters are consistent with Example 2.
[0047] Comparative Example 3: Comparative Example 3 is based on Example 2. No transition layer is introduced in Comparative Example 3, and the remaining process steps and reaction parameters are consistent with Example 2.
[0048] A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take a ceramic substrate, ultrasonically clean it with acetone solution for 12 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 12 minutes each, and blow dry with nitrogen; the ceramic substrate is a silicon nitride ceramic substrate, and its size is 50 mm×50 mm×0.32 mm; (2) Pre-cutting a solder guide groove on the edge of one side of the ceramic substrate by laser processing, wherein the width of the solder guide groove is 5 mm and the depth is 50 μm; washing with deionized water, drying, and then spin coating photoresist on the surface of the ceramic substrate, baking at 105° C. for 12 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the depth of the solder groove is 50 μm, and the solder groove and the solder guide groove are interconnected.
[0049] The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.8a.
[0050] Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; (3) Take graphene oxide and deionized water, and ultrasonically disperse them for 20 minutes to obtain a graphene oxide aqueous solution (1 mg / mL). Take 0.25 g of copper sulfate pentahydrate and 0.16 g of silver nitrate, mix them, add 10 mL of graphene oxide aqueous solution, 20 mL of deionized water, 10 mL of sodium citrate (0.02 mol / L) and sodium borohydride (0.2 mol / L), and stir the mixture at 28°C for 1.5 hours. After the reaction is completed, let it stand for 2.5 hours, filter and wash it, and vacuum dry it to obtain modified graphene.
[0051] Take 70wt% silver powder, 20wt% copper powder, 5wt% titanium hydride powder and 5wt% modified graphene, mix and stir evenly, grind for 8min, and ball mill for 45min at a speed of 170r / min to obtain solder powder, mix 88wt% solder powder and 12wt% organic carrier in a ratio, the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent, mix and stir evenly to obtain solder; the thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, the solvent is diethylene glycol dimethyl ether and pineneol, and the mass ratio of the two is 2:3.
[0052] Applying solder to the solder guide groove and the solder tank to obtain an active solder layer; the thickness of the active solder layer applied in the solder guide groove and the solder tank is 50 μm; Comparative Example 4: Comparative Example 4 is based on Example 2. In Comparative Example 4, it is defined that “when the preset circuit pattern width is a, the solder groove width is 0.9a”, and the remaining process steps and reaction parameters are consistent with Example 2.
[0053] A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take a ceramic substrate, ultrasonically clean it with acetone solution for 12 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 12 minutes each, and blow dry with nitrogen; the ceramic substrate is a silicon nitride ceramic substrate, and its size is 50 mm×50 mm×0.32 mm; (2) Pre-cutting a solder guide groove on the edge of one side of the ceramic substrate by laser processing, wherein the width of the solder guide groove is 5 mm and the depth is 55 μm; washing with deionized water, drying, and then spin coating photoresist on the surface of the ceramic substrate, baking at 105°C for 12 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the depth of the solder groove is 60 μm, and the solder groove and the solder guide groove are interconnected.
[0054] The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.9a.
[0055] Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; Comparative Example 5: Comparative Example 5 is based on Example 2. In Comparative Example 5, it is defined that “when the preset circuit pattern width is a, the solder groove width is 0.5a”, and the remaining process steps and reaction parameters are consistent with Example 2.
[0056] A method for preparing a copper-clad ceramic substrate comprises the following steps: (1) Take a ceramic substrate, ultrasonically clean it with acetone solution for 12 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 12 minutes each, and blow dry with nitrogen; the ceramic substrate is a silicon nitride ceramic substrate, and its size is 50 mm×50 mm×0.32 mm; (2) Pre-cutting a solder guide groove on the edge of one side of the ceramic substrate by laser processing, wherein the width of the solder guide groove is 5 mm and the depth is 55 μm; washing with deionized water, drying, and then spin coating photoresist on the surface of the ceramic substrate, baking at 105°C for 12 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the depth of the solder groove is 60 μm, and the solder groove and the solder guide groove are interconnected.
[0057] The pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.9a.
[0058] Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence, the ultrasonic cleaning time is 15 minutes each, and blow dry with nitrogen; Comparative Example 6: Comparative Example 6 is based on Example 2. Ultrasonic assisted brazing is not performed in Comparative Example 6, and the remaining process steps and reaction parameters are consistent with those of Example 2.
[0059] A method for preparing a copper-clad ceramic substrate comprises the following steps: (5) Repeat steps (2) to (4) to process interconnected solder grooves and solder guide grooves on the other side of the ceramic substrate, and apply a transition layer and an active solder layer, wash with deionized water, and dry; Take copper foil with a thickness of 50 mm × 50 mm × 0.4 mm, fix it on both sides of the ceramic substrate, and braze it at high temperature at a temperature of 930° C. and a vacuum degree of 5×10-4 Pa to obtain a copper-clad laminate; take the copper-clad laminate, perform circuit patterning processing, and etch a preset circuit pattern to obtain the copper-clad ceramic substrate.
[0060] Detection experiment: The copper clad laminate samples prepared in Examples 1-3 and Comparative Examples 1-6 were subjected to the following performance tests; the thermal shock test was carried out at -50°C × 10 min and 220°C × 10 min, with the temperature rise and fall controlled at 20 s, and the treatment was repeated 100 times, and the peel strength was retested and recorded.
[0061]
[0062] Conclusion: The copper clad laminate prepared in Examples 1-3 has no warping on the surface, and the circuits are clear and accurate, there is no solder overflow between the circuits, the copper clad laminate has excellent peeling strength, and there is no void as a whole; while the copper clad laminate prepared in Comparative Example 4 has slight solder residue between the circuits and no warping; the peeling strengths of the remaining Comparative Examples 1-3 and Comparative Examples 5-6 are inferior to that of the present application.
[0063] The process of the present invention is reasonably designed and simple to operate. The prepared copper-clad laminate has excellent strength, the ceramic substrate and the copper foil have good bonding performance, and the solder can be controlled during the processing of the copper-clad ceramic substrate to avoid overflow and diffusion. The product has an excellent overall appearance and a high yield, can be used for mass production, and has high practicality.
[0064] Finally, it should be noted that the above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above examples, those skilled in the art can still modify the technical solutions described in the above examples or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a copper-clad ceramic substrate, characterized in that: The following steps are involved: (1) Take the ceramic substrate, ultrasonically clean it with acetone solution for 10-15 minutes, then ultrasonically clean it with anhydrous ethanol and deionized water in sequence, the ultrasonic cleaning time is 10-15 minutes each, and blow dry it with nitrogen; (2) pre-cutting a solder guide groove on the edge of one side of the ceramic substrate, washing with deionized water, drying, and then spin-coating photoresist on the surface of the ceramic substrate, baking at 100-110° C. for 10-15 min, ultraviolet exposure, and development to expose the solder groove pattern, placing the ceramic substrate in an ICP etcher for ICP etching, and etching a solder groove on the surface of the ceramic substrate, wherein the solder groove and the solder guide groove are connected to each other; Take the ceramic substrate after ICP etching, remove the surface photoresist, and then use acetone, anhydrous ethanol, and deionized water ultrasonic cleaning in sequence. The ultrasonic cleaning time is 10-15 minutes, and then blow dry with nitrogen; (3) Take modified graphene, aluminum oxide, calcium carbonate, silicon carbide, and silicon nitride, mix them evenly, and then ball-mill them. Add dispersant, binder, and water, stir evenly to obtain a transition coating material, apply it to a solder tank, and sinter at a high temperature of 1500-1600°C for 30-40 minutes to obtain a transition layer. (4) Take silver powder, copper powder, titanium hydride powder and modified graphene, mix and stir evenly, grind for 5-10 minutes, and ball mill for 40-50 minutes at a speed of 160-180 r / min. After ball milling, add thickener, dispersant, solvent, antioxidant and thixotropic agent, mix and stir evenly to obtain solder; Applying solder to the solder guide groove and the solder groove, and covering the transition layer to obtain an active solder layer; (5) Repeat steps (2) to (4) to process interconnected solder grooves and solder guide grooves on the other side of the ceramic substrate, and apply a transition layer and an active solder layer, wash with deionized water, and dry; Take copper foil, fix it on both sides of the ceramic substrate, and braze it at high temperature to obtain a copper-clad board; take the copper-clad board, perform circuit patterning treatment, and etch a preset circuit pattern to obtain the copper-clad ceramic substrate.
2. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: In step (2), the thickness of the ceramic substrate is h, the width of the solder guide groove is 0-5 mm, and the depth is ≦0.5h; the depth of the solder groove is ≦0.5h, and the depth of the solder groove is greater than the depth of the solder guide groove.
3. The method for preparing a copper-clad ceramic substrate according to claim 2, characterized in that: In step (2), the thickness of the active solder layer coated in the solder groove and the solder guide groove is 30-50 μm, and the thickness of the transition layer is 5-10 μm.
4. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: In step (2), the difference in depth between the solder groove and the solder guide groove is 5-7 μm, and the solder guide groove is formed by any one of laser processing, ultrasonic grinding, electric spark processing, and electrolytic processing.
5. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: In step (2), the pattern of the solder groove is the same as the preset circuit pattern. When the width of the preset circuit pattern is a, the width of the solder groove is 0.6a~0.8a.
6. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: In step (5), the high temperature brazing temperature is 900-950°C and the vacuum degree is 5×10 -4 ~8×10 -4 Pa; ultrasonic vibration is applied to the surface of the copper foil during high-temperature brazing, the ultrasonic frequency is 20-25kHz, the power is 100-200w, and the ultrasonic time is 30-60s.
7. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The raw materials of each component of the transition layer include 90wt% powder and 10wt% organic solvent, the powder includes 8wt% modified graphene, 82wt% aluminum oxide, 4wt% silicon carbide, 5wt% silicon nitride, and 1wt% calcium carbonate; the organic solvent includes 4wt% dispersant, 3wt% binder and 93wt% water, the dispersant is sodium polyacrylate, and the binder is silica sol.
8. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The raw materials of each component in the solder include 88wt% solder powder and 12wt% organic carrier, the solder powder includes 70wt% silver powder, 20wt% copper powder, 5wt% titanium hydride powder and 5wt% modified graphene; the organic carrier includes 12wt% thickener, 5wt% dispersant, 70wt% solvent, 7wt% antioxidant and 6wt% thixotropic agent; The thickener is polyethylene glycol, the dispersant is stearic acid, the thixotropic agent is stearic acid amide, the antioxidant is oxalic acid, and the solvent is diethylene glycol dimethyl ether and terpineol in a mass ratio of 2:
3.
9. The method for preparing a copper-clad ceramic substrate according to claim 1, characterized in that: The modified graphene preparation method comprises: taking copper sulfate pentahydrate and silver nitrate, adding graphene oxide aqueous solution, deionized water, sodium citrate and sodium borohydride after mixing, stirring and reacting at 25-30° C. for 1-2 hours, standing for 2-3 hours after the reaction is completed, filtering and washing, and vacuum drying to obtain the modified graphene. 10 . A copper-clad ceramic substrate prepared according to the method for preparing a copper-clad ceramic substrate according to any one of claims 1 to 9 .
Citation Information
Patent Citations
Silicon nitride ceramic copper-clad substrate and preparation method thereof
CN114230361A
Method for improving warping of copper-clad ceramic substrate mother board
CN114478044A
Active metal brazing copper-clad ceramic substrate and preparation method thereof
CN114853497A
Preparation method of multilayer copper-clad ceramic substrate
CN117279218A
Engineered polymer electronic materials
JP2018518544A
Cited By
Pyrolytic graphite and aluminum alloy high-strength metallurgical material containing gradient transition layer and preparation method of pyrolytic graphite and aluminum alloy high-strength metallurgical material
CN122076957A
Method for thinning brazing layer of copper-clad ceramic substrate
CN122210147A